Surface Treatment of Dental Mini-Sized Implants and Screws: A Systematic Review with Meta-Analysis - Ana Luísa Figueiredo; Raquel Travassos; Catarina Nunes; Madalena Prata Ribeiro; Mariana Santos; Flavia Iaculli; Anabela Baptista Paula; Carlos Miguel Marto; Francisco Caramelo; Inês Francisco; Francisco Vale (Journal of Functional Biomaterials, 2024)
Miniscrews are devices that allow for absolute skeletal anchorage. However, their use has a higher failure rate (10–30%) than dental implants (10%). To overcome these flaws, chemical and/or mechanical treatment of the surface of miniscrews has been suggested. There is no consensus in the current literature about which of these methods is the gold standard; thus, our objective was to carry out a systematic review and meta-analysis of the literature on surface treatments of miniscrews. The review protocol was registered (PROSPERO CRD42023408011) and is in accordance with the PRISMA guidelines. A bibliographic search was carried out on PubMed via MEDLINE, Cochrane Library, Embase and Web of Science. The initial search of the databases yielded 1684 results, with 98 studies included in the review, with one article originating from the search in the bibliographic references of the included studies. The results of this systematic review show that the protocols of miniscrew surface treatments, such as acid-etching; sandblasting, large-grit and acid-etching; photofunctionalization with ultraviolet light; and photobiomodulation, can increase stability and the success of orthodontic treatment. The meta-analysis revealed that the treatment with the highest removal torque is SLA, followed by acid-etching. On the other hand, techniques such as oxidative anodization, anodization with pre-calcification and heat treatment, as well as deposition of chemical compounds, require further investigation to confirm their effectiveness.